Regulatory gaps in private supplementary tutoring: international patterns and implications for social protection - Bray, Mark (Frontiers in Education, 2025)
The present century has brought marked expansion of private supplementary tutoring across countries of all income levels. Tutoring is provided in diverse modes by commercial enterprises, full-time teachers seeking extra incomes, and informal suppliers ranging from senior-secondary students to retirees. As tutorial enrolment rates rise, receipt increasingly becomes a necessity for keeping up with peers. However, this creates inequalities: the lowest-income families are excluded entirely, while those slightly higher in the income hierarchy cannot access the quantities and qualities of tutoring accessed by wealthier families. These patterns also raise multi-layered issues. At the level of the child are matters of the quality of tutoring and basic safety in inadequately-supervised environments. At the parental level are matters of fees, honesty in marketing, etc.; and at the broad social level are inequalities that challenge what UNESCO has called a desirable social contract. All these dimensions require effective regulation.